Individual Differences in the Deterrence Process: Which Individuals Learn (Most) from Their Offending Experiences? - Schulz, Sonja (Journal of quantitative criminology, 2014)
Objectives To test whether individuals differ in deterrability by studying whether the effect of criminal experiences on perceived detection risk varies by criminal propensity. Methods Data from the British “Offending, Crime and Justice Survey”, a four-wave panel study on criminal behavior and victimization, are analyzed. Two subsamples for analyses are constructed: one of non-offenders at first measurement, to analyze the effect of gaining first offending experiences during the time of study ( n = 1,279) and one sample of individuals who have committed offenses within the past year ( n = 567), to analyze the effect of police contact among active offenders. Fixed-effects regressions of perceived detection risk on criminal experiences and interactions between criminal experiences and measures of criminal propensity (risk-affinity, impulsivity) are estimated. Results Analyses support learning models for the formation and change of risk perceptions, but individual differences by criminal propensity are present in the deterrence process: After gaining first offending experiences, impulsive individuals as well as risk-averse individuals are more likely to lower their perceptions about the probability of detection than less impulsive or risk-affine individuals are. A positive effect of police contact on expected detection risk is restricted to risk-averse individuals. Conclusions Findings support claims that deterrence works differently for crime-prone individuals. The differential effects of impulsivity and risk-affinity underline the importance of not combining constituent characteristics of criminal propensity in composite indices, because they might have differential effects on deterrence.